OP21 COVID-19 vaccine-induced antibody responses are impaired in Inflammatory Bowel Disease patients treated with infliximab, ustekinumab or tofacitinib, but not thiopurines or vedolizumab. (21st January 2022) - Alexander, J; Kennedy, N; Ibraheim, H; Anandabaskaran, S; Saifuddin, A; Castro Seoane, R; Liu, Z; Nice, R; Bewshea, C; D'Mello, A; Constable, L; Jones, G R; et al.
Abstract: Background: Robust COVID-19 vaccine-induced antibody (Ab) responses are important for protective anti-viral immunity. Data are urgently needed to determine whether vaccine-induced immunity is impacted by commonly used immunosuppressive drug regimens in IBD. Methods: We prospectively recruited 447 adults (90 healthy controls and 357 IBD) at nine UK centres. The IBD study population was established (>12 weeks therapy) on either thiopurine monotherapy (n=78), infliximab (IFX) monotherapy (n=61), thiopurine & IFX combination therapy (n=70), ustekinumab (uste) monotherapy (n=56), vedolizumab (vedo) monotherapy (n=62) or tofacitinib (tofa) monotherapy (n=30). Participants had two doses of either ChAdOx1 nCoV-19, BNT162b2 or mRNA1273 vaccines. The primary outcome was anti-SARS-CoV-2 spike (S1 RBD) Ab concentrations, measured using the Elecsys anti-SARS-CoV-2 spike (S) Ab assay, 53–92 days after second vaccine dose, in participants without prior infection, adjusted by age & vaccine type. Secondary outcomes included proportions failing to generate protective Ab responses (defined cut-off anti-S concentration 15U/mL, which correlated with 20% viral neutralization). Results: Geometric mean S Ab concentrations (figure 1) were lower in patients treated with IFX (153U/mL;p<0.0001), IFX and thiopurine combination (109U/mL;p<0.0001), tofa (430U/mL;p<0.0001) and uste (561U/mL;p=0.013) compared to controls (1596U/ml). No differences in S Ab concentrations were found between controls and thiopurine monotherapy-treated patients (1020U/mL;p=0.62), nor between controls and vedo-treated patients (944 U/mL;p=0.69). In multivariable modelling (figure 2), lower S Ab concentrations were independently associated with IFX (FC 0.10 [95% CI 0.07–0.14], p<0.0001), tofa (0.36 [95% CI 0.19–0.69], p=0.002) and uste (0.56 [95% CI 0.31–1.00], p=0.049), but not with thiopurine (0.77 [95% CI 0.54–1.11], p=0.17) or vedo (1.01 [95% CI 0.61–1.68], p=0.96). mRNA vaccines (3.67 [95% CI 2.72–4.96], p<0.0001) and older age (0.82 [95% CI 0.73–0.91], p=0.0003) were independently associated with higher & lower S Ab concentrations respectively. Protective Ab responses were generated by all thiopurine monotherapy, vedo, tofa and healthy control participants, but not by 11% of patients on IFX monotherapy, 13% on thiopurine & IFX combination therapy and 4% on uste. Conclusion: COVID-19 vaccine-induced Ab responses are significantly reduced in patients treated with IFX, or tofa, and to a lesser extent with uste. No significant reduction was seen in vedo or thiopurine monotherapy-treated patients. Our data suggest that 3rd primary or booster vaccine doses for IBD patients might be tailored to an individual's immunosuppressive treatment. Financial support was provided as a Research Grant by Pfizer Ltd.